Influence of Borides on microstructure and mechanical properties of a Ni alloy - Kaya, Esad; Buytoz, Soner (Walter de Gruyter Gmbh, 2024)
Ni alloys are known to exhibit superior creep strength, chemical stability, and thermal resistance behavior at elevated temperatures. However, they also exhibit inadequate mechanical performance. Hence, the microstructures and, in relation to that, mechanical properties need to be improved. In this study, the effect of reinforcement of TiB2 on microstructural and mechanical properties was evaluated. The Ni matrix is reinforced with TiB2 particles. TiB2-Ni composites were successfully produced by the hot pressing method. Homogenously distributed TiB2 particles were observed in the microstructure using the energy dispersive spectrometry (EDS) mapping technique. The hardness of the reinforced samples was considerably improved by 2.65-8.12 times compared to pure Ni and between the different content of borides. A three-point bending test was performed to examine the mechanical behaviors of the reinforced composites. The bending stress properties of metal matrix composite (MMC) were significantly influenced by TiB2 content both positively and adversely. The optimum chemical content was determined based on bending tests and fractography. As a result, the 15wt.% TiB2-reinforced sample exhibited superior microstructural (density), hardness, and bending properties compared to pure Ni and other reinforced samples with different ratios.
Keywords: fractography; mechanical testing; metallic matrix; powder metallurgy; sintering